Factors Determining Adoption Of Internet Banking Among Consumers In Malaysia - Wai, Shang Ye (2009)
This research paper aims to study the level of awareness of Internet banking benefits, to analyze the perceived ease of use by the Internet banking customers and to identify if the knowledge and awareness of Internet security help to speed up the adoption of Internet banking among banking customers in Malaysia.